PERBEDAAN TEKANAN DARAH BERDASARKAN KEIKUTSERTAAN SENAM PADA LANSIA DI INSTALASI GERIATRI RSUP DR. KARIADI SEMARANG TAHUN 2017 - Merry Putri R. Sirait; Lintang Dian Saraswati; Ari Udiyono; Martini Martini (Jurnal Kesehatan Masyarakat (Undip), 2018)
Hypertension is the highest non-infectious disease in Indonesia with proportion 25.8%. Health Profile of Semarang City on 2015 showed hypertension in elderly reach 34%. Hypertension in the elderly is a disease that requires special attention and control to preventcomplications disease. The purpose of this study is to describe the blood pressure based on several factors that affect the elderly in the Geriatric Installation of RSUP Dr. Kariadi Semarang. This research use cross sectional method. The sample of this research is 70 people. The results show that majority of female respondents (71,4%), have age 60-69 years old (70.%), member of elderly gymnastic (68,8%), have no family history of hypertension (60%), have normal nutritional status (55,7%), have central obesity (60%), The highest average of blood pressure was found in respondent who not a member of elderly gymnastic(136,59/81,09 mmHg), have family history of hypertension(140,96/81,55 mmHg),have central obesity (135,64/80,95 mmHg), Awareness-raising needs to be taken to keep lifestyle and increase liveliness in following elderly gymnastics routinely to reduce complications from hypertension.